Młode wino do starych bukłaków? Stan i perspektywy badań regionalnych dotyczących historii Niemców w Polsce - Krzoska, Markus (Biblioteka Uniwersytecka w Poznaniu, 2012)
Jest to tekst wykładu, którym dr Markus Krzoska uświetnił otwarcie wystawy zorganizowanej w Bibliotece Uniwersyteckiej. Zdecydowaliśmy się na jego przedruk z zachowaniem wszystkich retorycznych osobliwości właściwych dla języka mówionego (przyp. red.)

The script of the lecture delivered at the University Library in January 2011. Dr Krzoska’s lecture was occasioned by the opening of the exhibition organized by the Library: “Region and nation. A 125 years of German historiography and study of the geography, civilization and the history of German people in Poznań and Poland”.
Young wine in old wineskins? The current state and the perspectives of regional studies in the history of the Germans in Poland